The Impact of Financial Structure on Profitability of Croatian Companies - Učkar, Dean; Urti, Josip (Oeconomica Jadertina, 2017)
This paper explores the impact which different formation of financial and capital structure has on the achievement of companies' financial results. The establishment of this relationship is very important because there are many theories of capital structure that in its settings have a proposition on existence or non-existence of such a link. With that goal in mind, it is selected a sample of 24 companies whose shares are listed on the Zagreb Stock Exchange and are part of the CROBEX index. Their financial statements are analyzed through three years, from year 2011 till the year 2013. Through the analysis of company's liabilities, this paper present the average structure of debt financing, and thereby establish some regularities in the sources of their funding. Through the calculation of debt and profitability indicators, it is established a relationship between financial structure and achieved profitability. Such a connection is established through correlation coefficients and it found that it is inversely proportional. Indirectly, this reject the validity of those capital structure theories that basically say there is no link between the combination of funding sources and the value of the company
Keywords: financial structure; capital structure; debt financing; financial analysis